2022
DOI: 10.2147/ott.s364545
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Features of Primary Renal Well-Differentiated Neuroendocrine Tumor

Abstract: Primary carcinoid tumor of the kidney is an extremely rare well-differentiated neuroendocrine tumor, which is generally a low-grade malignant cancer with a good prognosis. Carcinoid tumors are rarely found in the urinary system. Here, we report a 34-year-old woman with primary renal well-differentiated neuroendocrine tumor who underwent nephron sparing surgery and no evidence of recurrence or distant metastasis was found during routine follow-up. We searched the case of renal carcinoid with the search phrase “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Certain seemingly primary renal carcinoids can constitute a metastatic focus from an undiscovered primary lesion (8)(9)(10)(11). Previous studies support a hypothesis, also known as the co-existence hypothesis, which proposes that the proliferation of scattered neuroendocrine cells originates from the epithelium of a horseshoe or polycystic kidney (12,13). It has been found that the risk of developing carcinoids in the horseshoe kidney is 62-to 82-fold higher than that noted in the normal kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Certain seemingly primary renal carcinoids can constitute a metastatic focus from an undiscovered primary lesion (8)(9)(10)(11). Previous studies support a hypothesis, also known as the co-existence hypothesis, which proposes that the proliferation of scattered neuroendocrine cells originates from the epithelium of a horseshoe or polycystic kidney (12,13). It has been found that the risk of developing carcinoids in the horseshoe kidney is 62-to 82-fold higher than that noted in the normal kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Cytologically, the tumor cells exhibit fine granular “salt-and-pepper” chromatin patterns. Immunohistochemical markers such as CgA, Syn, neuron-specific enolase (NSE), and CD56 are valuable for diagnosing PRNTs ( 15 ). Surgical resection is the primary treatment for PRNTs, and several prognostic factors associated with a poor prognosis have been identified, including age at diagnosis greater than 40 years, severe initial symptoms, tumor diameter greater than 4 cm, tumor extension through the renal capsule, and presence of metastasis at the initial diagnosis ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Krishnan et al, individuals with horseshoe kidney have around 62 times higher risk of developing NETs (5). Though the pathogenesis of carcinoid tumors of kidney has been debatable, el-Naggar et al found a loss of heterozygosity at one locus on chromosome 3p21 and hypothesized that this aberration, which is common in renal cell carcinoma (RCC), is a precursory event shared by all renal neoplasms, including carcinoid tumors (6). The most widely used functional imaging technique for cancer detection is fluorodeoxyglucose-PET (FDG-PET).…”
Section: Discussionmentioning
confidence: 99%